Method for directly adsorbing carbon dioxide from air and co-producing nano sodium bicarbonate

By utilizing the nanopore domain limit effect in the hydrogel film of sodium hydroxide and polyvinyl alcohol aqueous solution, carbon dioxide is directly adsorbed from the air and nano-sodium bicarbonate is solved, and the inconvenience of adsorption of sodium hydroxide aqueous solution and preparation of nano-sodium bicarbonate is prepared by using the nanopore limit effect in the hydrogel film of sodium hydroxide aqueous solution. Complex problems have achieved efficient and low-cost carbon dioxide adsorption and nano-sodium bicarbonate production.

CN119219030APending Publication Date: 2024-12-31SUZHOU YUXIN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411334023.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the aqueous sodium hydroxide solution as a carbon dioxide adsorbent has problems such as inconvenience in static adsorption, small surface area, low adsorption efficiency and solvent volatility, and the preparation process of nano-sodium bicarbonate is complicated and the particle size control is difficult.

Method used

By preparing sodium hydroxide and polyvinyl alcohol aqueous solution, a hydrogel film material is formed, and it is repeatedly frozen and thawed in a low-temperature refrigerator. The nanopore domain limit effect of the hydrogel is used to directly adsorb carbon dioxide from the air and dissolve it through hot water. Nano sodium bicarbonate.

Benefits of technology

The curing of sodium hydroxide and efficient adsorption of carbon dioxide are achieved. Combined with the film-forming properties of polyvinyl alcohol and the nanopore structure of hydrogel, an efficient and convenient adsorption effect is achieved, and the raw material cost and process complexity are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219030A_ABST
    Figure CN119219030A_ABST
Patent Text Reader

Abstract

The invention discloses a method for directly adsorbing carbon dioxide from air and co-producing nano sodium bicarbonate. A hydrogel film is prepared from a sodium hydroxide aqueous solution and a polyvinyl alcohol aqueous solution, and the sodium hydroxide aqueous solution is stably locked by utilizing abundant hydroxyl groups, so that the sodium hydroxide solution is cured, and the problems of solvent loss and the like of a liquid sodium hydroxide adsorbent are solved. In addition, the high-strength polyvinyl alcohol hydrogel thin film increases the surface area of the liquid film, so that the adsorption efficiency is favorably improved. The polyvinyl alcohol is rich in hydrogen bonds, and excellent water locking property is combined with the hygroscopicity of sodium hydroxide, so that the material does not have weightlessness or solvent loss in an environment with the relative humidity of 80%. The raw materials adopted by the invention are low in cost, the preparation process is simple and convenient, and the cost performance is relatively high. And finally, by virtue of the water solubility of the polyvinyl alcohol and the nanopores of the hydrogel, the nano sodium bicarbonate can be directly generated and easily separated, and a product with a high additional value is produced while the carbon dioxide is captured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new material preparation, and specifically relates to a method for preparing nanometer materials by adsorbing carbon dioxide. Background Art

[0002] Climate change is a huge challenge facing all mankind. Global warming caused by greenhouse gas emissions not only threatens the balance of natural ecosystems, but also threatens human survival. Carbon dioxide (CO2), one of the most influential greenhouse gases, has seen a significant increase in emissions since the Industrial Revolution due to the widespread use of fossil fuels, bringing severe climate change challenges to the world.

[0003] Carbon capture and storage (CCS) is considered a promising technology for reducing CO2 emissions. Through the application of various CCS technologies, CO2 emissions can be significantly reduced even if relatively cheap and abundant fossil fuels such as coal are continued to be used. At the peak stage of carbon emissions, high-quality peaking needs to be balanced with the sustainable development of the economy and society. As an important means of reducing emissions, carbon capture technology can effectively alleviate the pressure during the peak period of carbon emissions.

[0004] At present, a variety of CO2 capture technologies have been developed, including absorption methods using solid adsorbents or solvents (such as amines and alkali solutions), membrane separation technology, and cryogenic distillation. The adsorption method using solid adsorbents selectively adsorbs CO2 in a gas mixture and then desorbs and concentrates it under specific conditions. Chemical absorption is the most widely used and technologically mature method. It uses chemical solvents to undergo a reversible chemical reaction with CO2 to achieve the absorption and desorption of CO2. Membrane separation technology separates and classifies substances by utilizing particle size and pressure differences. The cryogenic separation method is based on the difference in volatility of each gas in the flue gas. By repeatedly compressing and condensing the flue gas, CO2 reaches a critical value, thereby converting it from a gaseous state to a liquid state and separating it from the gas mixture.

[0005] Most post-combustion treatment plants currently use monoethanolamine (MEA) as an adsorbent. However, due to the high volatility of MEA and the solvent degradation that occurs during the absorption process, regular replenishment is required.

[0006] CO2 can also be captured by absorption into an aqueous solution of sodium hydroxide (NaOH). In fact, the CO2 absorption capacity of NaOH solution is higher than that of MEA. Theoretically, the amount of MEA and NaOH required to capture one ton of CO2 is 1.39 tons and 0.9 tons, respectively. In addition, NaOH is more abundant and cheaper than MEA.

[0007] Enrique et al. used solid sodium hydroxide as an adsorbent for carbon dioxide (Enrique Medina-Martos et al., Environmental and economic performance of carbon capture with sodium hydroxide, Journal of CO 2 Utilization 60 (2022) 101991).

[0008] The Chinese patent application number CN201710424451.1 discloses a method for preparing a high-efficiency carbon dioxide adsorbent based on alkali residue. The alkali residue is dried, crushed and then sieved. The sieved particles are collected, impurities are removed, and then mixed with sodium carbonate for filtration. The filter residue is collected, dried, and ball-milled and calcined with sodium borate and tetrabutyl titanate. The calcined product is mixed with anhydrous ethanol and the like and then centrifuged. The lower precipitate is collected, stirred and preheated with isopropanol, isomaltooligosaccharide, etc., and then stirred with sodium hydroxide solution to discharge the material. The collected discharge is allowed to stand and filtered, and the filter residue is washed, freeze-dried and crushed. Finally, the sieved particles are collected through a sieve to obtain a carbon dioxide adsorbent.

[0009] However, solid sodium hydroxide is prone to absorb moisture in the air and deliquesce. Static adsorption using liquid sodium hydroxide aqueous solution has a small surface area and is inconvenient. Dynamic spray adsorption requires a special spray device, which consumes a lot of energy and is expensive. In addition, the use of sodium hydroxide aqueous solution for adsorption has the problem of solution volatilization.

[0010] Nano sodium bicarbonate is widely used in many fields due to its ultrafine particles and high specific surface area. In environmental protection, it is used as an efficient flue gas desulfurization and deacidification agent to help reduce the emission of harmful gases; in medical treatment, it is used as a buffer and antacid to regulate the acid-base balance of the human body; the cosmetics industry uses its mild exfoliating properties to improve the cleansing effect. In addition, nano sodium bicarbonate can also be used as a catalyst carrier to increase the rate of chemical reactions, and in the food industry, it plays the role of a leavening agent to improve the texture of food. Its unique nanoscale structure enables it to show superior performance than ordinary sodium bicarbonate in these fields. The preparation methods of nano sodium bicarbonate mainly include precipitation method, solution method and mechanical crushing method. The precipitation method generates nanoparticles by controlling the reaction conditions of sodium carbonate and carbon dioxide, while the solution method obtains nano sodium bicarbonate through dissolution and precipitation processes. The mechanical crushing method uses a high-energy ball mill to crush sodium bicarbonate to the nanoscale. However, these methods have certain disadvantages, such as easy agglomeration of particles, high production costs, uneven particle size distribution, poor stability, and possible environmental pollution in some processes. Effectively solving these problems is the key to large-scale application of nano sodium bicarbonate. Summary of the invention

[0011] The present invention aims to provide a method for directly adsorbing carbon dioxide from the air and co-producing nano sodium bicarbonate to solve the problems of static adsorption, inconvenient placement, small surface area, low adsorption efficiency and solvent volatilization of sodium hydroxide aqueous solution as carbon dioxide adsorbent, as well as the complex process for preparing nano sodium bicarbonate and difficulty in controlling particle size in the prior art. The method for directly absorbing carbon dioxide in the air and co-producing nano sodium bicarbonate comprises the following steps: a first step, respectively preparing a sodium hydroxide aqueous solution with a mass fraction of 5wt% to 40wt% and a polyvinyl alcohol aqueous solution with a mass fraction of 3wt% to 10wt%; a second step, mixing the two aqueous solutions at a mass ratio of 1:1; a third step, coating the aqueous solution obtained in the previous step on a stainless steel plate, placing the plate in a low-temperature refrigerator at -120°C to -40°C and performing repeated freeze-thaw cycles for 5 times to obtain a hydrogel film material; a fourth step, using the hydrogel film material to directly absorb carbon dioxide from the air, and utilizing the nanopore confinement effect of the hydrogel to obtain nano sodium bicarbonate in the pores of the hydrogel; and a fifth step, after carbon dioxide adsorption is saturated, dissolving the hydrogel film material in hot water at 90°C to 98°C to dissolve the polyvinyl alcohol, and then centrifuging to obtain nano sodium bicarbonate.

[0012] The sodium hydroxide aqueous solution of the present invention is in the nanopores of the polyvinyl alcohol hydrogel, and under the combined action of huge capillary force and sodium hydroxide, the sodium hydroxide aqueous solution is solidified without liquid leakage, and the absorbed carbon dioxide reacts with the sodium hydroxide in the nanopores to obtain sodium bicarbonate, and nano sodium bicarbonate is obtained due to the nano confinement effect of the nanopores of the hydrogel. After adsorption saturation, the material is placed in hot water to dissolve the polyvinyl alcohol, and then centrifuged to obtain nano sodium bicarbonate.

[0013] Beneficial effects: The present invention introduces an aqueous sodium hydroxide solution into the nanopores of the hydrogel, and a strong capillary force (the smaller the pore size, the greater the capillary force) firmly locks the solution, thereby achieving the solidification of the sodium hydroxide solution, so that the block material has both the high efficiency of a liquid adsorbent and the convenience of a solid adsorbent. In addition, polyvinyl alcohol has good film-forming properties and high strength, and is widely used as a concrete reinforcing material. The polyvinyl alcohol hydrogel film of the present invention has a large surface area and high strength, and is expected to efficiently adsorb carbon dioxide from the air. In addition, due to the nanoporous structure of the hydrogel and the hygroscopicity of sodium hydroxide, the material will not lose weight or suffer solvent loss in air with a relative humidity of 80%. In addition, the raw materials used in the present invention are low in price, the preparation process is simple, and it has a high cost-effectiveness ratio. Finally, due to the confinement effect of the nanopores, the present invention can directly generate nano sodium bicarbonate, achieving the production of high-value products while adsorbing carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The raw materials used in this application and the hydrogel films prepared.

[0015] Figure 2 The nano sodium bicarbonate prepared in Example 1. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work still fall within the scope of protection of the present invention. Example 1

[0017] The first step is to prepare a sodium hydroxide aqueous solution with a mass fraction of 5wt% and a polyvinyl alcohol aqueous solution with a mass fraction of 3wt% respectively; the second step is to mix the above two aqueous solutions in a mass ratio of 1:1; the third step is to apply the aqueous solution obtained in the previous step on a stainless steel plate, and place it in a -120°C low-temperature refrigerator and freeze-thaw it repeatedly for 5 times to obtain a hydrogel film material; the fourth step is to use the above hydrogel film material to directly adsorb carbon dioxide from the air, and utilize the nanopore confinement effect of the hydrogel to obtain nano sodium bicarbonate in the pores of the hydrogel; the fifth step is to dissolve the hydrogel film material in hot water at 90°C to 98°C after the carbon dioxide adsorption is saturated, dissolve the polyvinyl alcohol, and then centrifuge to obtain nano sodium bicarbonate, and the average particle size of the obtained nano sodium bicarbonate is 86nm. Example 2

[0018] The first step is to prepare a sodium hydroxide aqueous solution with a mass fraction of 10wt% and a polyvinyl alcohol aqueous solution with a mass fraction of 5wt% respectively; the second step is to mix the above two aqueous solutions in a mass ratio of 1:1; the third step is to apply the aqueous solution obtained in the previous step on a stainless steel plate, and place it in a -100°C low-temperature refrigerator and freeze-thaw it repeatedly for 5 times to obtain a hydrogel film material; the fourth step is to use the above hydrogel film material to directly adsorb carbon dioxide from the air, and utilize the nanopore confinement effect of the hydrogel to obtain nano sodium bicarbonate in the pores of the hydrogel; the fifth step is to dissolve the hydrogel film material in hot water at 90°C to 98°C after the carbon dioxide adsorption is saturated, dissolve the polyvinyl alcohol, and then obtain nano sodium bicarbonate by centrifugation, and the average particle size of the obtained nano sodium bicarbonate is 81nm. Example 3

[0019] The first step is to prepare a sodium hydroxide aqueous solution with a mass fraction of 15wt% and a polyvinyl alcohol aqueous solution with a mass fraction of 6wt% respectively; the second step is to mix the above two aqueous solutions in a mass ratio of 1:1; the third step is to apply the aqueous solution obtained in the previous step on a stainless steel plate, and place it in a -80°C low-temperature refrigerator and freeze-thaw it repeatedly for 5 times to obtain a hydrogel film material; the fourth step is to use the above hydrogel film material to directly adsorb carbon dioxide from the air, and utilize the nanopore confinement effect of the hydrogel to obtain nano sodium bicarbonate in the pores of the hydrogel; the fifth step is to dissolve the hydrogel film material in hot water at 90°C to 98°C after the carbon dioxide adsorption is saturated, dissolve the polyvinyl alcohol, and then obtain nano sodium bicarbonate by centrifugation, and the average particle size of the obtained nano sodium bicarbonate is 73nm. Example 4

[0020] The first step is to prepare a sodium hydroxide aqueous solution with a mass fraction of 20wt% and a polyvinyl alcohol aqueous solution with a mass fraction of 8wt% respectively; the second step is to mix the above two aqueous solutions in a mass ratio of 1:1; the third step is to apply the aqueous solution obtained in the previous step on a stainless steel plate, and place it in a -70°C low-temperature refrigerator and freeze-thaw it repeatedly for 5 times to obtain a hydrogel film material; the fourth step is to use the above hydrogel film material to directly adsorb carbon dioxide from the air, and utilize the nanopore confinement effect of the hydrogel to obtain nano sodium bicarbonate in the pores of the hydrogel; the fifth step is to dissolve the hydrogel film material in hot water at 90°C to 98°C after the carbon dioxide adsorption is saturated, dissolve the polyvinyl alcohol, and then obtain nano sodium bicarbonate by centrifugation, and the average particle size of the obtained nano sodium bicarbonate is 67nm. Example 5

[0021] The first step is to prepare a sodium hydroxide aqueous solution with a mass fraction of 30wt% and a polyvinyl alcohol aqueous solution with a mass fraction of 9wt% respectively; the second step is to mix the above two aqueous solutions in a mass ratio of 1:1; the third step is to apply the aqueous solution obtained in the previous step on a stainless steel plate, and place it in a -60°C low-temperature refrigerator and freeze-thaw it repeatedly for 5 times to obtain a hydrogel film material; the fourth step is to use the above hydrogel film material to directly adsorb carbon dioxide from the air, and utilize the nanopore confinement effect of the hydrogel to obtain nano sodium bicarbonate in the pores of the hydrogel; the fifth step is to dissolve the hydrogel film material in hot water at 90°C to 98°C after the carbon dioxide adsorption is saturated, dissolve the polyvinyl alcohol, and then obtain nano sodium bicarbonate by centrifugation, and the average particle size of the obtained nano sodium bicarbonate is 61nm. Example 6

[0022] The first step is to prepare a sodium hydroxide aqueous solution with a mass fraction of 40wt% and a polyvinyl alcohol aqueous solution with a mass fraction of 10wt% respectively; the second step is to mix the above two aqueous solutions in a mass ratio of 1:1; the third step is to apply the aqueous solution obtained in the previous step on a stainless steel plate, and place it in a -40°C low-temperature refrigerator and freeze-thaw it repeatedly for 5 times to obtain a hydrogel film material; the fourth step is to use the above hydrogel film material to directly adsorb carbon dioxide from the air, and utilize the nanopore confinement effect of the hydrogel to obtain nano sodium bicarbonate in the pores of the hydrogel; the fifth step is to dissolve the hydrogel film material in hot water at 90°C to 98°C after the carbon dioxide adsorption is saturated, dissolve the polyvinyl alcohol, and then centrifuge to obtain nano sodium bicarbonate, and the average particle size of the obtained nano sodium bicarbonate is 54nm.

Claims

1. A method for directly adsorbing carbon dioxide from the air and co-producing nano sodium bicarbonate, characterized in that it comprises the following steps: a first step, respectively preparing a sodium hydroxide aqueous solution and a polyvinyl alcohol aqueous solution; a second step, mixing the two aqueous solutions in a mass ratio of 1:1; a third step, coating the aqueous solution obtained in the previous step on a stainless steel plate, and placing it in a low-temperature refrigerator and repeatedly freezing and thawing for 5 times to obtain a hydrogel film material; a fourth step, using the hydrogel film material to directly adsorb carbon dioxide from the air, and utilizing the nanopore confinement effect of the hydrogel to obtain nano sodium bicarbonate in the pores of the hydrogel; a fifth step, after carbon dioxide adsorption is saturated, dissolving the hydrogel film material in hot water to dissolve the polyvinyl alcohol, and then centrifuging to obtain nano sodium bicarbonate.

2. according to claim 1, a method for co-producing nano sodium bicarbonate by directly adsorbing carbon dioxide from air, the mass fraction of the sodium hydroxide aqueous solution is 5wt%~40wt%.

3. According to claim 1, a method for co-producing nano sodium bicarbonate by directly adsorbing carbon dioxide from air, wherein the mass fraction of the polyvinyl alcohol aqueous solution is 3wt% to 10wt%.

4. According to claim 1, a method for co-producing nano sodium bicarbonate by directly adsorbing carbon dioxide from air, the temperature of the low-temperature refrigerator is -120°C to -40°C.

5. According to claim 1, a method for co-producing nano sodium bicarbonate by directly adsorbing carbon dioxide from air, the temperature of the hot water is 90°C to 98°C.

6. According to claim 1, a method for co-producing nano sodium bicarbonate by directly adsorbing carbon dioxide from air, wherein the average particle size of the nano sodium bicarbonate is 54nm to 86nm.